(untitled) (ENTHYMEMA, 2017)
In this paper I want to trace briefly how Franz Kafka reacted to some salient cultural features of his time. I will select segments of his writings which I believe reflect his view, or even his characterization of the three main historical periods he lived through: pre-World War I, the war years 1914 to 1918, and five and one half of the postwar years. Of course, this is by no means a complete, thorough discussion of those periods and his works that I mention.